91 GATIFLOXACIN PRODUCES BOTH HYPOGLYCEMIA AND HYPERGLYCEMIA: A RETROSPECTIVE STUDY. Issue 1 (1st January 2007) - Haerian, H.; McHugh, P.; Somes, G.; Solomon, S.
Abstract : Fluoroquinolones are now the most commonly prescribed antibiotic among adults in the United States. Recent studies have shown a propensity for one of these drugs, gatifloxicin, to produce hypoglycemia. Bristol-Myers Squibb Company ceased marketing this drug on May 1, 2006. To examine further the effects of gatifloxicin (G) on blood glucose (BS) in inpatients, we conducted a retrospective chart review on 264 subjects, examining for both hypo- and hyperglycemia, comparing G with another quinolone, ciproflaxin (C), and a nonquinolone, ceftriaxone (R). We found that of 292 patient encounters, 28 hypoglycemic and 48 hyperglycemic events were identified. After adjustment for three confounding variables, we found that patients given G were five times as likely to become hypoglycemic as C ( p < .01) and nine times as likely as those given R ( p < .02), with no difference between C and R. If we combined those given R or C into one group, those given G were 5.6 times more likely to develop hypoglycemia, p < .001. On the other side of the issue, patients treated with G were 3.8 times as likely to become hyperglycemic as those given C ( p < .01), and 9.8 times as likely as those given R ( p < .01). With C and R combined, those given G were 5.2 times as likely to develop hyperglycemia ( p < .01). Furthermore, looking at patient encounters in which G was given, we found that having preexisting DM was positively associated with hypoglycemia (21/144, p < .001). Steroid use ( p < .05) and being in the ICU ( p < .01) were also positively associated with hyperglycemia (38/144, p < .01). In summary, G was clearly associated with both hypoglycemia and hyperglycemia compared with other antibiotics (C and R). The risk of hyperglycemia was increased in the presence of DM, steroid use, and "sick enough" to be in the ICU.